The Determinants of Liquidity Risk in Islamic Banks: A Case of Sudanese Banking Sector - Mennawi, Ahmed Nourrein Ahmed; Ahmed, Ahmed Ali (International Journal of Islamic Banking and Finance Research, 2020)
Liquidity risk either due to a surplus or serious shortage in liquidity has a significant impact to the performance and sustainability of Islamic banks. Nevertheless, there are still no common agreement on specific factors that determine the liquidity risk in Islamic banking. This study investigates the determinant factors that affect the liquidity risk of Sudanese Islamic banks. A sample of 11 banks has been selected for a period of 7 years (2012 – 2018). The study is based on secondary data that analysed using Pearson correlation and multiple regression analysis for hypotheses tests. It investigated the explanatory variables of the bank’s cash position (CASH), investment in short-term securities (SECA), degree of financing the assets from customers’ deposits (DPAS) and bad financing and credit risk (NPL) as representatives of banks’ specific factors plus one microeconomic factor which is Gross Domestic Product (GDP). The analysis found a significant and negative relation of CASH and SECA with the liquidity risk in Islamic banks. On the other hand, the results reveal that the DPAS and NPL variables have a positive relation and significant, while the GDP seen to be irrelevant to liquidity risk in Islamic bank. The importance of the study is that it touches the most significant type of risk that most of Sudanese Islamic banks face, and the data analysed covers a relatively longer period of time than similar studies for a single country. We target that the study contributes in providing decision-makers with reasonable ground for prediction and managing the liquidity risk. JEL Classification: G21, G17, G32.